Control of Seed-borne Disease (Octomeles Sumatrana) during Storage - NFN Nurhasybi; Tati Suharti (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
The forest tree species that are widely grown to produce pulp and paper raw materials are Acacia spp. and Eucalyptus spp. One alternative species is binuang bini (Octomeles sumatrana) which can be developed for plantations. To maintain high seed viability, it is necessary to know the handling of seeds and control of seed-borne diseases during storage. The purpose of this study was to determine the method of the effective technique to control the seed-borne diseases of binuang bini during seed storage. The techniques for Seed disease kontrol methods in seed storage are carried out using chemical and natural fungicide. The results showed that the pure live seed was influenced by a single factor of fungicide and storage room, interactions between fungicides and storage room, interactions between fungicides and storage periods as well as interactions between fungicides and storage space and storage periods. Seed handling of binuang bini can be conducted effectively and efficiently by storing the seed in refrigerator for 3 months without using fungicides, but it will be better if the seed is given benomil fungicide and stored in airconditioned room (temperature of 18℃-20℃ and relative humidity of 50%-60 %).